Toward improved stroke care in Nepal: insights from a qualitative study on barriers and success factors - Tunkl, Christine; Paudel, Raju; Thapa, Lekhjung; Shreyan, Shirsho; Krauß, Alexandra; Subedi, Ashim; Karmacharya, Balgopal; Jalan, Pankaj; Haji Begli, Nima; Tunkl, Patrick; Bajaj, Sunanjay; Kosinski, Andrea; et al. (Frontiers in neurology, 2025)
BackgroundThe Nepal Stroke Project (NSP) aims to improve stroke care in a resource-limited setting. This qualitative study explores healthcare professionals’ experiences and perceptions of barriers and success factors in implementing stroke care in Nepal.MethodsSemi-structured interviews were conducted with eight healthcare professionals (six physicians, two nurses) involved in the NSP. Interviews were analyzed using qualitative content analysis, following a constructivist approach.ResultsSuccess factors encompassed the dedication of healthcare professionals, involvement of hospital boards, effective training initiatives, and the formation of stroke teams. Positive developments noted were increased thrombolysis availability, improved stroke awareness, and growing interest in stroke care among medical professionals. Key barriers identified included lack of government ownership in stroke care advocacy, financial constraints for patients, inadequate public awareness, and challenges in implementing quality monitoring.ConclusionWhile the NSP has initiated positive changes in Nepal’s stroke care landscape, significant barriers persist. The study highlights the importance of addressing systemic issues such as government involvement and financial accessibility of treatments. Success factors, particularly the motivation of healthcare professionals and local ownership of the project, provide a foundation for future improvements. These findings can inform strategies for enhancing stroke care delivery in other resource-limited settings and guide ongoing initiatives within the NSP.
Online veröffentlicht: 7. August 2025
Gesehen am 25.02.2026